MRI findings and utility of DWI in the evaluation of solid parathyroid lesions - Yildiz, Seyma; YILDIZ, ŞEYMA; Aralasmak, AYŞE; ARALAŞMAK, AYŞE; YETIS, Huseyin; KILICARSLAN, Rukiye; Sharifov, RASUL; SHARIFOV, RASUL; Alkan, ALPAY; ALKAN, ALPAY; Toprak, HÜSEYİN; TOPRAK, HÜSEYİN (My University, 2019)
Purpose To evaluate the MRI findings of solid parathyroid lesions and to elaborate on a possible improvement of MRI detection of parathyroid lesions by the use of additional DWI.